2004
DOI: 10.1038/sj.npp.1300489
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence for the Tonic Activation of 5-HT1A Autoreceptors in the Rat Dorsal Raphe Nucleus

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) and norepinephine (NE) neurons have reciprocal connections. These may thus interfere with anticipated effects of selective pharmacological agents targeting these neurons. The main goal of the present study was to assess whether the somatodendritic 5-HT 1A autoreceptor is tonically activated by endogenous 5-HT in anesthetised rats, using in vivo extracellular unitary recordings. In rats with their NE neurons lesioned using 6-hydroxydopamine (6-OHDA) and in controls administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 48 publications
7
41
2
2
Order By: Relevance
“…The 5-HT 1A autoreceptor was then shown to mediate 5-HT auto-inhibition [7,12]. A consistent observation has been that reduction or ablation of 5-HT 1A autoreceptors leads to increased 5-HT neurotransmission [13][14][15][16][17], while over-expression of 5-HT 1A autoreceptors reduces 5-HT neurotransmission [18][19][20]. While 5-HT 1A antagonists do not greatly affect basal firing, they consistently reverse inhibition of firing by 5-HT 1A agonist or specific reuptake inhibitor (SSRI) treatment, suggesting that the basal level of 5-HT under recording conditions may be insufficient to see effects.…”
Section: -Ht 1a Autoreceptors As Brakes For 5-ht Neurotransmissionmentioning
confidence: 99%
“…The 5-HT 1A autoreceptor was then shown to mediate 5-HT auto-inhibition [7,12]. A consistent observation has been that reduction or ablation of 5-HT 1A autoreceptors leads to increased 5-HT neurotransmission [13][14][15][16][17], while over-expression of 5-HT 1A autoreceptors reduces 5-HT neurotransmission [18][19][20]. While 5-HT 1A antagonists do not greatly affect basal firing, they consistently reverse inhibition of firing by 5-HT 1A agonist or specific reuptake inhibitor (SSRI) treatment, suggesting that the basal level of 5-HT under recording conditions may be insufficient to see effects.…”
Section: -Ht 1a Autoreceptors As Brakes For 5-ht Neurotransmissionmentioning
confidence: 99%
“…The selective 5-HT1A-R antagonist, WAY 100 635 (0, 40, or 400 mg/kg), was co-administered intravenously with nicotine or saline. These doses were selected because they do not modify spontaneous firing of 5-HT neurons or basal locomotor activity (Carey et al, 2001;Haddjeri et al, 2004). The selective nAChR antagonists, DHbE (2 mg/kg) and MLA (1 mg/kg), were administered intravenously 5 min before daily nicotine pretreatment.…”
Section: -Day Pretreatmentmentioning
confidence: 99%
“…In addition, WAY-100635 has been described as a "silent" 5-HT 1A antagonist, a term that has been used to distinguish true antagonists from partial agonists (23,24). Although a few studies have shown effects of WAY-100635 alone on behavior (56) and 5-HT neuronal firing rate (29,30) when microinjected into the dorsal raphé, the role of intrinsic 5-HT 1A agonists in the tonic control of medullary raphé 5-HT neuronal firing rate remains unclear.…”
Section: -Oh-dpat Dialysis Into the Medullary Raphé Decreases Periphmentioning
confidence: 99%